Window of opportunity treatment in breast cancer. Issue 1 (26th November 2019) - Chen, Julia; Easwaralingam, Neshanth; Warrier, Sanjay; Ong, Andrew; Carson, Emma‐Kate; Mak, Cindy; Snook, Kylie; Middleton, Kate; Parker, Andrew; Palmieri, Carlo; Spillane, Andrew; Mann, G. Bruce; et al.
Abstract: Window of opportunity therapies, which involve short‐term administration of systemic therapy between cancer diagnosis and surgery, have raised significant interest in recent years as a mean of assessing the sensitivity of a patient's cancer to therapy prior to surgery. There is now compelling evidence that in patients with early stage hormone‐receptor positive breast cancer, a 2‐week preoperative treatment with standard hormone therapies in a preoperative window period provides important prognostic information, which in turn helps to aid decision‐making regarding treatment options. Changes in short‐term biomarker endpoints such as cell proliferation measured by Ki‐67 can act as surrogate markers of long‐term outcomes. Paired tissues obtained pre‐ and post‐investigational treatment, without having to subject the patient to additional biopsies, can then be used to conduct translational research to investigate predictive biomarkers and pharmacodynamics. In this review, we will examine the utility and challenges of window of opportunities therapies in breast cancer in the current literature, and the current Australian and international trial landscape in this clinical space. Abstract : Window of opportunity therapies involve short‐term administration of systemic therapy between cancer diagnosis and surgery. There is now compelling evidence that in patients with early stage hormone‐receptor positive breast cancer, a 2‐week preoperative treatment with standard hormone therapies in a preoperative window period provides important prognostic information, which in turn helps to aid decision‐making regarding subsequent treatment options.